Patellar tendinosis: Acute patellar tendon rupture and jumper's knee - dePalma, M. J.; Perkins, R. H. (The Physician and Sportsmedicine, 2004)
Patellar tendinopathy (jumper's knee) may affect athletes who engage in explosive lower-limb movements. An eccentric contraction of the quadriceps when landing after a jump may lead to acute patellar tendon rupture, the end-stage of patellar tendinopathy. Plain x-rays will usually confirm the diagnosis. Treatment centers around reducing the stress placed on the patellar tendon. Postoperative functional restoration and preventive measures must address biomechanic abnormalities that may predispose patients to disruptive patellar tendon strain. As this case report shows, counseling patients who have early-stage tendinopathy on appropriate flexibility and plyometric exercises may prevent more serious damage.